JENIS DAN POPULASI BAKTERI ICE NUCLEATION ACTIVE PENYEBAB LUKA BEKU PADA DAUN JERUK KEPROK SOE DI DATARAN TINGGI MUTIS - Hildegardis Missa; Anselmus Boy Baunsele (Agro Bali : Agricultural Journal, 2020)
Research on ice nucleation-active bacteria causes frost injury from tropic areas has not been widely publicized. The purpose of this study was to determine the population of Ice Nucleation-Active Bacteria on Soe tangerines leaves and the class of Ice Nucleation-Active bacteria based on Ice formation temperatures. The collecting of Soe tangerine leaves used the purpose sampling method. Leaves with frost blotches were collected from three stages at altitudes of 1500, 1800, and 2000 meters above sea level (m asl). Bacterial isolation was carried out by the spread plate method on Nutrien Agar 2,5 % glycerol (NAG)  media. Ice Nucleation activity was determined by the tube nucleation test method. Estimation of INA bacterial population was conducted by the multiple-tube nucleation test with Thomas series .3.3.3. The result showed that the highest INA bacterial population was 6.9x104 which was found in leaves samples collected from stations 1800 and 2000 m asl, and the lowest population i.e. 5,4x103 on leaf samples from station 1500 m asl. Based on the temperature of ice formation, it was known that INA bacteria that attack the Soe tangerines leaves Mutis plateau are the INA bacteria class B and C.